A single S1034C mutation confers altered drug sensitivity to PfMDR1 ATPase activity that is characteristic of the 7G8 isoform - Amoah, L.E.; Lekostaj, J.K.; Roepe, P.D. (Molecular and Biochemical Parasitology (1): 107-11, 2008)
The mechanism behind how PfMDR1 may contribute to antimalarial drug resistance is unclear. Transfection studies suggest that PfMDR1 mutations may make small contributions to drug sensitivity in a strain-dependent fashion, whereas field data link over expression (not necessarily mutation) of the gene with clinical drug treatment failure. This study dissects the contribution of individual mutations of PfMDR1 that contribute to the unique behavior of the 7G8 PfMDR1 isoform. A single mutation in putative TM 11 (S1034C) is found to abolish drug stimulation of PfMDR1 ATPase activity.